Samba: from the social margin to national identity (Revista Internacional de Folkcomunicação, 2023)
The union between Europeans and Africans modeled a samba-body of unique characteristics impregnated in the Brazilian imagination. The idea is to prove that samba, a product marginalized by the elites, has become a symbol of Brazilianness, a national identity. At first, brief historical, social and political contexts are traced from the 1910s to the 1940s in relation to the history and evolution of samba in Brazil. In a second moment, we bring the construction of the body through samba. Cultural studies theory was used as a basis for historical investigation. This study was carried out through socio-historical analyzes in articles and books, which would allow the interpretation of the representations built around the passage of the meaning of samba, its music and popular dance for a representation of Brazilian culture.Keywords: Samba, Cultural study, Body-Samba, afrodescendant, Rio de Janeiro
Keywords: African descent; Body-samba; Cultural study; Samba.